Crystallization and preliminary X‐ray crystallographic analysis of the inhibitory domain of the tomato mosaic virus resistance protein Tm‐1. Issue 12 (1st December 2013) - Kato, Masahiko; Kezuka, Yuichiro; Kobayashi, Chihoko; Ishibashi, Kazuhiro; Nonaka, Takamasa; Ishikawa, Masayuki; Katoh, Estuko
<x xml:space="preserve">Abstract</x> Tm‐1, an inhibitor protein of Tomato mosaic virus RNA replication, contains two conserved domains: an uncharacterized domain at its N‐terminus and a TIM‐barrel‐like domain at its C‐terminus. The N‐terminal domain of Tm‐1 has an inhibitory activity and its three‐dimensional structure has not been determined. Here, the crystallization and preliminary X‐ray diffraction of the N‐terminal domain of Tm‐1 are reported. A three‐wavelength MAD data set was collected from a selenomethionine‐labelled crystal and processed to 2.7 Å resolution. The crystal belonged to the triclinic space group P1, with unit‐cell parameters a = 77.97, b = 105.28, c = 110.62 Å, α = 94.6, β = 109.3, γ = 108.0°.